Discovery of pathogenesis related and effector genes of Erwinia mallotivora in Carica papaya (Eksotika I) seedlings via transcriptomic analysis - Juri, Nor Mustaiqazah; Samsuddin, Aimera Farhana; Abdul Murad, Abdul Munir; Tamizi, Amin Asyraf; Shaharuddin, Noor Azmi; Abu Bakar, Norliza (Friends Science Publishers, 2020)
A comparative transcriptome of Erwinia mallotivora library across early infection time points (6, 24 and 48 h) on papaya seedling Carica papaya (Eksotika I) was performed. A total of 5,680 genes were identified as differentially expressed genes (DEGs). The highest numbers of DEGs in all three E. mallotivora infection time points were accounted in the biosynthesis of secondary metabolites, microbial metabolism in diverse environments and ATP binding cassette transporters based on KEGG-based analysis. The functional annotation of the DEGs via Gene Ontology analysis has revealed a highly complex (more than 2,000 functional terms) yet a specific virulence strategy adapted by E. mallotivora across the infection time points. Our findings have uncovered the key factors and pathogenicity mechanism adopted by E. mallotivora as the infection progresses.